Health Benefits of Honey: Knowledge, Attitude and Perception (KAP) Among the Community in Malaysia - Wan Nor Aidah Basirah Wan Ab Rahman; Syarifah Syamimi Putri Adiba Syed Putera; Aina Amanina Abdul Jalil (Asian Journal of Medicine & Health Sciences, 2023)
Background: Honey is a sticky, jelly-like natural substance produced by honeybees (Apis mellifera; Apidae) from blossom nectar. According to current scientific research, honey may be beneficial and protective in treating various medical illnesses. Objective: This study aimed to identify usage patterns of honey among Malaysian and evaluate their KAP toward the health benefits of honey. Method: A cross-sectional study was conducted using a self-administered, face-validated online questionnaire distributed among 400 participants aged 18 years and above recruited using convenience sampling between January and May 2022. The questionnaire consists of five domains: demographic characteristics, honey’s usage pattern, knowledge, attitude, and perception of the health benefits of honey. Sections 1 and 2 consist of multiple-choice questions while each KAP part comprises 2-7 items Likert scale questions. The overall score for each KAP section is calculated and the level is classified by using Bloom’s cut-off point. The statistical analysis methods for this study were analyzed using the SPSS version 23. Descriptive statistics were performed using SPSS version 22 and the data were presented in frequency and percentage. Results: Most of the respondents were single (83.9%), female (58%) university students (36.5%) with bachelor’s degree (66%). Among Malaysian, Tualang (n=218) is the most frequently consumed honey for the purpose of suppressing cough (n=342) with an expenditure of more than RM60 per month (n=162). Results also showed that participants have a good knowledge (n=185, 46.3%), optimistic attitude (n=275, 68.8%) and positive perception (n=276, 69%) toward the health benefit of honey. Conclusion: The majority of the study participants were knowledgeable about honey and awareness of its benefit must be directed to the public.